2017
DOI: 10.1080/10410236.2017.1407228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Color, Imagery, and Text of Cigarette Package Warning Labels among Socioeconomically Disadvantaged Middle School Youth and Adult Smokers

Abstract: The U.S. Family Smoking Prevention and Tobacco Control Act (Tobacco Control Act) of 2009 paved the way for the Food and Drug Administration (FDA) to propose nine different graphic warning labels (GWLs) intended for prominent placement on the front and back of cigarette packs and on cigarette advertisements. Those GWLs were adjudicated as unconstitutional on the ground that they unnecessarily infringed tobacco companies' free speech without sufficiently advancing the government's public health interests. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 28 publications
(41 reference statements)
0
33
1
Order By: Relevance
“…Research associates first led participants through a brief eyetracking calibration procedure in order to collect data on visual attention to the stimuli as part of a separate series of studies. We do not include eyetracking data in this paper, as these measures do not pertain to the current hypotheses (see Byrne et al, 2017; Skurka et al, 2017). Participants next viewed the experimental stimuli (nine cigarette pack images, described below) then self-reported negative affect, beliefs about the health risks of smoking, quit intentions (or susceptibility to smoking for youth), other covariates, and demographics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research associates first led participants through a brief eyetracking calibration procedure in order to collect data on visual attention to the stimuli as part of a separate series of studies. We do not include eyetracking data in this paper, as these measures do not pertain to the current hypotheses (see Byrne et al, 2017; Skurka et al, 2017). Participants next viewed the experimental stimuli (nine cigarette pack images, described below) then self-reported negative affect, beliefs about the health risks of smoking, quit intentions (or susceptibility to smoking for youth), other covariates, and demographics.…”
Section: Methodsmentioning
confidence: 99%
“…We modified the original, FDA-proposed GWLs slightly by removing the telephone quit line and using the same font for all nine images. We report the main effect results of these manipulations elsewhere (Byrne et al, 2017; Skurka et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The special issue reports on 10 studies examining various aspects of communication regulatory science. Studies examine originally-regulated products such as cigarettes ( Byrne et al, 2018 ; Lazard et al, 2018 ; Moran et al, 2018 ) and smokeless tobacco ( Wackowski, Manderski, Lewis, & Delnevo, 2018 ) as well as new and emerging products such as e-cigarettes ( Cornacchione Ross, Noar, & Sutfin, 2018 ; Kim, Popova, Halpern-Felsher, & Ling, 2018 ; Mays, Villanti, Niaura, Lindblom, & Strasser, 2018 ; Moran et al, 2018 ; Walter, Demetriades, & Murphy, 2018 ; Yang, Liu, Lochbuehler, & Hornik, 2018 ), little cigars and cigarillos ( Cornacchione Ross et al, 2018 ; Moran et al, 2018 ; Sutfin et al, 2018 ), and waterpipe tobacco ( Cornacchione Ross et al, 2018 ; Sutfin et al, 2018 ). It includes studies that can inform the FDA in several areas of communication, and is organized in three sections.…”
Section: Special Issue Contentmentioning
confidence: 99%
“…Product warnings have been an important tool for communicating with the public about tobacco product risk, and such warnings have become stronger over time as research has revealed some of the more effective elements ( Hiilamo, Crosbie, & Glantz, 2014 ; Noar et al, 2017 ). Byrne and colleagues examine responses to variations of text and pictorial cigarette warnings among socioeconomically disadvantaged middle school youth and smokers, testing whether less extensive alternatives that could be more acceptable to the courts–such as text-only or black and white pictorial warnings–would achieve the same goal as color pictorial warnings ( Byrne et al, 2018 ). They report mixed findings regarding whether a less extensive alternative could achieve the government’s interest of communicating the health effects of smoking and reducing cigarette smoking, with color pictorial warnings out-performing less extensive alternatives on some outcomes but faring similarly on others.…”
Section: Special Issue Contentmentioning
confidence: 99%